BUDIDAYA JAMUR TIRAM DENGAN MEDIA KULIT BUAH KOPI UNTUK PELUANG USAHA BAGI WANITA TANI KELURAHAN TALANG ULU KABUPATEN REJANG LEBONG - Irma Badarina; Nadrawati Nadrawati; Endang Sulistyowati (Jurnal Hilirisasi IPTEKS, 2020)
Talang Ulu sub-district in Rejang Lebong regency Bengkulu is one of the agriculture type village based on coffee plantation. The families income were really depended on the stability of coffee prices. About 50% the families were the low income people (LIP) category. Most of the farming activity were done by man. While the women only managed the household. The time for farmer women to do the activity out of the household are still possible. After all the household activities were done, the women farmer could do another activity to get additional income such as the oyster mushroom cultivation. The oyster mushroom cultivation is easy to do and cheap enough. The solid substrate for mushroom can use the coffee husk that are widely available in the location. The aim of this community service activity was to train the farmer women in Talang Ulu sub-district about the oyster mushroom cultivation. The methods were the counseling and the direct practice in oyster mushroom cultivation. The mushroom house as demonstration plot was made for practicing how to take care of and did the the mushroom business. This community service activity had increased their knowledge in mushroom cultivation. The oyster mushroom cultivation became the bussines opportunity being annoying the daily household activity. The animo of the farmer women were good enough that can be seen by making a mushroom cultivation group. They aspire to have their own mushroom business later.